Clinical characteristics of diabetic patients attending for the first time a nephrologic consultation in Lima public hospitals - Herrera Añazco, Percy (2014)
Introduction: Diabetes mellitus is the leading cause of chronic renal disease; early referral to the nephrologist is recommended as the outcome is worse in patients with late referral. Objectives: To determine clinical characteristics of diabetic patients upon their first nephrologic consultation. Design: Multicenter, observational and analytical study. Setting: Hospital Nacional 2 de Mayo, Hospital Nacional Arzobispo Loayza, Hospital Daniel Alcides Carrion and Hospital Maria Auxiliadora. Participants: Diabetic patients. Interventions: Diabetic patients were studied between September 2011 and February 2012. Percentages were used to describe frequencies and standard deviations. Main outcome measures: Clinical characteristics of diabetes patients. Results: From 200 diabetic patients with 12.9 years mean time to diagnosis 73% had received education for self-care, 40% reported not taking their medications and 57% did not follow a regular diet; 70% were hypertensive with 4.2 years average from time of diagnosis, 36.5% were obese, 52.8% had dyslipidemia; 10.5% had a history of cardiovascular disease, and 81.5% reported no prior assessment of renal function; 39.5% had glycated hemoglobin (HbA1c) >7%, 48.5% cholesterol >200 mg/dL, 54.5% LDLc >100 mg/dL, and 46.5% triglycerides >150 mg/dL. Fifty seven per cent had a glomerular filtration rate <60 mL/min, and 37% albuminuria 300 mg/d or more. Conclusions: Almost half of all patients did not follow self-care recommendations. Due to substantial cardiovascular risk factors involved, education of this group should be strengthened.